Prolonged luteal phase support with progesterone may increase papules and plaques of pregnancy frequency in pregnancies through in vitro fertilization, - Nur Dokuzeylul Gungor; Tugba Gurbuz; Tugba Ture (Sociedade Brasileira de Dermatologia, 2021)
Abstract Background: Pruritic urticarial papules and plaques of pregnancy development may have a strong relationship with hormone treatments during in vitro fertilization and hormonal changes during pregnancy. Objectives: The aim of this study was to evaluate and compare the frequency of papules and plaques of pregnancy and related factors in in vitro fertilization pregnancies and spontaneous pregnancies. Methods: In this study, 517 in vitro fertilization pregnancies and 1253 spontaneous pregnancies were retrospectively reviewed for papules and plaques of pregnancy frequency. The diagnosis of papules and plaques of pregnancy was performed by referral to the dermatology department and according to the typical clinical manifestations of the disease. Results: The papules and plaques of pregnancy was more common in all in vitro fertilization pregnancies (including single pregnancies) than in spontaneous pregnancies. Age, Rh positivity, mother weight gain, onset of disease during gestation, duration of disease, birth weight and the frequency of male fetus were similar between the two groups (p > 0.05). The rate of multiple pregnancies was higher in in vitro fertilization pregnancies with papules and plaques of pregnancy than in vitro fertilization pregnancies without papules and plaques of pregnancy (p < 0.001). Duration of progesterone treatment was also significantly longer in in vitro fertilization pregnancies with papules and plaques of pregnancy compared to in vitro fertilization pregnancies without papules and plaques of pregnancy (p < 0.001). Study limitations: The limitations of the study were the retrospective and single-centered design. Conclusion: The results of this study indicate that increased progesterone dosage or prolonged treatment may play a role in the pathogenesis papules and plaques of pregnancy.